"Estética" de la armonía en Platón - Alvarado Dávila, Víctor (2005)
The present essay has the aim of paying attention to some of I. Kant’s main thesis on education.Particularly, the concept and purpose of education, the limits of education as an art and the capital elements in the building of moral culture, fundamental support a of good and happy human life.